Framework for the Packaging Supply Chain of an Automotive Engine Company - Vöröskői, K; Böröcz, P (Acta Technica Jaurinensis, 2016)
Automotive industrial groups consider the impacts of packaging very important, mainly focusing on the cost effectiveness and environmentally conscious nature thereof. In the literature, the packaging supply chain is not a significantly researched area as regards the supply of the complete automotive engines. But the selection of packaging and the relevant development process in engine production are among the main elements of the extensive automotive industry, because participants sometimes have the same interests and considerations. This way, decision-making and strategies on using different packaging solutions and systems can be very varied. The reason is that each automotive group practically produces its own engines and transports them to their assembling subsidiaries all over the world. These groups often apply similar logistics policies and supply systems to use, take-back and recover their packaging. This is being driven as much by group strategies as it is by the need to reduce costs and increase efficiency in supply chains. The focus of this paper will be on the components and elements of packaging supply chain management in the field of engine supply for automotive industry groups, and on how the decision-making framework is determined. This paper shows models defining the network process for decision-making within the automotive groups as regards the packaging supply chain.